(untitled) (Research, Society and Development, 2020)
Objective: Meta-analyze the proportion of condomless sex traded on the Internet according to the offer on websites advertising sex work and demand in customer forums; and to examine the relationship between condomless sex and the type of sex, target-group, gender and actors involved. Methodology: Data was collected from PubMed, Scielo, Google Scholar and ScienceDirect from the inception of each database to 06 March 2020, in English, Spanish and Portuguese. The effect size was the proportion itself, and the dispersion was measured under 95% confidence intervals. Results: From 2041 articles, 16 studies met the inclusion criteria of the systematic review with 10,190 recruited individuals and 20,363 prostitution advertisements. The estimate of condomless sex trade was 0.25 (95%CI=0.17–0.34). The heterosexual-oral subgroup (0.35; 95%CI=0.18–0.52; p<0.001) and the clients (0.31; 95%CI=0.20–0.59; p=0.037) showed a significant increase in the proportion. Conclusion: The condomless sex trade was reported in one quarter of the population. Heterosexuals who practice oral sex and clients are the main predictors of condomless sex in the Internet-based sex work.